The tail wagging the dog: positive attitude towards livestock guarding dogs do not mitigate pastoralists’ opinions of wolves or grizzly bears - Kinka, Daniel; Young, Julie K. (DigitalCommons@University of Nebraska - Lincoln, 2019)
While the re-establishment of grizzly bears (Ursus arctos) and wolves (Canis lupus) in the American West marks a success for conservation, it has been contentious among pastoralists. Coincidentally, livestock guarding dogs (LGDs; Canis familiaris) have been widely adopted by producers of domestic sheep (Ovis aries) in the United States to mitigate livestock depredation by wild carnivores. We surveyed pastoralists to measure how experience with and attitudes towards LGDs related to attitudes towards livestock predators, and found positive responses regarding LGDs and negative responses regarding wolves and grizzly bears. The more respondents agreed that LGDs reduce the need for lethal management (p < 0.01) and prevent the spread of disease (p < 0.05), the more positive their opinion of wolves in the wild. Regarding wolves and livestock, respondents who disagreed with the statements that “LGDs do more harm than good” (p < 0.05) or “reduce the need for lethal management” (p < 0.001), were more likely to express more negative opinions of wolves. While results pertaining to a reduced need for lethal management may suggest LGDs have some ability to increase tolerance for wolves, the causal order of these effects is difficult to discern. A more positive attitude for wolves to begin with may predict more optimistic attitudes about the capacity of LGDs to reduce human–wildlife conflict. We found almost no support for the opinion that LGDs do more harm than good, even though attitudes towards wolves were generally negative. Respondents with up to 10 years’ experience using LGDs had more negative attitudes towards grizzly bears (p < 0.01) and respondents with more than 10 years’ experience using LGDs had the most negative attitudes towards grizzly bears (p < 0.001). Thus, while experience was the greatest predictor of attitudes towards grizzly bears, attitudes towards wolves were most correlated with the belief that LGDs offset the need for lethal management of carnivores. These results suggest that LGD ...